(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
The aim of the paper was to describe pitch range modulation in yes-no questions in Ekegusii. In addition to describing the realization of intonation-related features like upstep and fundamental frequency (F0) in these questions, the paper has related this realization to the age and gender variables, to show how varied speakers’ speech is acoustically different. Data were collected from 24 purposively selected native speakers of Ekegusii (12 male and 12 female of different age groups). They were analysed within the framework of the Autosegmental-Metrical Theory. Two findings emerged from the analysis. First, the male speakers’ pitch range modulation was realised at an F0 bottom line of 126 Hz and top line of 242 Hz while the female speakers’ F0 bottom line was 225 Hz and top line 260 Hz. Second, although female speakers produced the utterances at higher F0s than their male counterparts did, there were variations across the four age groups of male and female speakers. The largest variation in F0 occurred among the youth and the smallest among the children. The advanced-aged female group of participants and the male children’s group produced the highest F0s while the middle-aged groups (both the female and the male) produced the lowest F0.